Considerations and techniques in the treatment of persons with multiple personality disorder. - Fike ML (American Journal of Occupational Therapy, 1990)
Occupational therapy intervention with the patient with multiple personality disorder requires an understanding of the complex psychotherapeutic goals for the patient and of the process involved in resolution of the trauma that led to the development of multiple personality. The psychotherapeutic techniques of hypnosis and abreaction affect the provision of occupational therapy services. Hypnotic communication, particularly the use of ideomotor hand signals, often facilitates work with various alter personalities. Occupational therapists may use a development approach with both child and adult alter personalities and may also use projective techniques, self-care training, and role and task management techniques. Occupational therapy can act as a stabilizing force for the person with multiple personality disorder through the enhancement of function and competency during the psychotherapeutic process.